Ultrasonographic manifestations and the effective diagnosis of epididymal leiomyosarcoma: Case report and systematic literature review - Song, Ruixiao; Xi, Jing; Shi, Honglei; Xue, Zhixin; Li, Huifang; Yu, Xiaolong (Frontiers in Oncology, 2023)
Background: Epididymal leiomyosarcoma is an extremely rare tumor. In this study, we describe the sonographic features of this uncommon tumor. Methods: A case of epididymal leiomyosarcoma diagnosed at our institute was retrospectively analyzed. Ultrasonic images, noted clinical manifestations, treatment procedures, and pathology results were collected for this patient. The same information was collected from a systematic literature search on epididymal leiomyosarcoma, including the PUBMED, Web of Science and Google Scholar databases. Results: The literature search resulted in 12 articles; we were able to extract data from 13 cases of epididymal leiomyosarcomatosis. The median patient age was 66 (35–78) years, and the average tumor diameter was 2–7 cm. All patients had unilateral epididymal involvement. The lesions were all solid, irregular-shaped in almost half of the cases, featured clear borders in six cases, and had unclear borders in four cases. The internal echogenicity was heterogeneous in the majority of lesions: six cases were hypoechoic (7/11) and three cases moderately echoic (3/10). Information on blood flow within the mass was provided in four cases, but all were noted with significant vascularity.. Surrounding tissue invasion was discussed in 11 cases, with 4 featuring peripheral invasion or metastasis. Conclusion: Epididymal Leiomyosarcoma demonstrates sonographic characteristics common to many malignant tumors, such as increased density, irregular shape, heterogeneous internal echogenicity, and hypervascular. Ultrasonography is helpful to differentiate benign epididymal lesions, and can provide some reference for clinical diagnosis and treatment. However, compared with other malignant tumors of the epididymis, it has no characteristic sonographic features,and pathological confirmation is required.